Bank Competition and Financial Stability in Nepal - Bandana Khanal (Journal of Corporate Finance Management and Banking System, 2024)
This paper examines the casual relationship between bank competition and financial stability in Nepal. The relationship between competition and financial stability in banking system can be explain by two hypothesis: The "competition-fragility" theory holds that increased bank competition weakens profit margins, undermines market power, and lowers franchise value—the continuing concern or market worth of the banks above their book values and “competition-stability” view contends that financial institution stability may benefit from competition. The study used descriptive and causal research design. The random effect panel data of 6 commercial banks of Nepal over the period of 2014-2019. All the data are obtained from NRB monthly statistic and bank annual report. The HHI and n-bank concertration ratio are used as a measure of bank competition while Z-Index and non-performing loan ratio are the proxies of financial stability. The findings confirm the"Competition-frangility" theory by showing a negative association between bank competition and financial stability in Nepal. It states that bank tends to take excessive risks when the competition level increases. It is discovered that competition in the banking industry raises credit risk and reduces capital levels. Riskier policies enhance the likelihood of increased bank bankruptcies and non-performing loan ratios, which adds to fragility and financial instability. Thus, less concentrated banking systems are prone to experiences crisis.